2020
DOI: 10.3390/coatings10040402
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Polypyrrole/V2O5 Composite Film on the Surface of Magnesium Using a Mild Vapor Phase Polymerization (VPP) Method for Corrosion Resistance

Abstract: The vapor phase polymerization (VPP) method is a conventional strategy for synthesizing conducting polymers (CPs) on the surfaces of various materials. However, the current VPP method performed on a metal surface usually requires harsh reaction conditions, such as high temperature and low vacuum. In this paper, a polypyrrole (PPy) and vanadium pentoxide (V2O5) composite film was synthesized on the surface of Mg using a mild VPP method. Here, V2O5 was used as an oxidant, and it was found that the oxidation of p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 31 publications
(41 reference statements)
0
6
0
Order By: Relevance
“…Majumdar et al 96 and Hanif et al 97 described VPP as an easy, inexpensive, and effective method of depositing CP coating onto a particular substrate. The main advantage of VPP is that it is a solvent‐free synthesis in which the monomers are applied as vapor rather than a solution, and no liquid acts as transport medium for particle agglomeration 94,95,98 . Nevertheless, most CPs produced using this method suffers from insufficient conductivity that limits their use as current path in electronic devices 94,99 .…”
Section: Synthesis Of Ppymentioning
confidence: 99%
See 1 more Smart Citation
“…Majumdar et al 96 and Hanif et al 97 described VPP as an easy, inexpensive, and effective method of depositing CP coating onto a particular substrate. The main advantage of VPP is that it is a solvent‐free synthesis in which the monomers are applied as vapor rather than a solution, and no liquid acts as transport medium for particle agglomeration 94,95,98 . Nevertheless, most CPs produced using this method suffers from insufficient conductivity that limits their use as current path in electronic devices 94,99 .…”
Section: Synthesis Of Ppymentioning
confidence: 99%
“…Results show that the conductivities of PPy films range within 10 −3 to 10 −2 S/cm. The thickness and pore size of PPy film increase from 5.3 to 23.0 μm and 1.3 to 7.2 μm with increased concentration of FeCl 3 from 0.05 to 0.5 M. Meanwhile, Li et al 98 used a mild VPP method to prepare PPy films, in which vanadium pentoxide (V 2 O 5 ) acts as the oxidant and metal magnesium (Mg) acts as the substrate. Polymerization reaction time is 12 h. They discovered that the oxidation of Py vapor on the surface of V 2 O 5 (precoated onto Mg surface) could be performed at room temperature under normal atmospheric pressure.…”
Section: Synthesis Of Ppymentioning
confidence: 99%
“…A significant decrease in the corrosion rate and corrosion current density of the PANI/coal coatings was observed suggesting that the coating is a promising candidate for the enhancement of corrosion resistance of Mg alloys in aggressive environments. In a research study by Li et al [125], a PPy/V 2 O 5 composite film was deposited on magnesium by mild vapor phase polymerization (VPP) technique. Corrosion investigations in 3.5 wt% NaCl revealed that the prepared composite film reduced the corrosion rate of Mg.…”
Section: Ccps Coated On Magnesium and Its Alloysmentioning
confidence: 99%
“…Another major class of applications of CPs is based on their compositiondependent properties. These reaction-driven properties have been exploited to find their application in sensors, [15][16][17] super capacitors, [18][19][20][21] batteries, 22,23 electrochromic devices, 4,24 artificial muscles, [25][26][27] corrosion protection, 28 and so on. The compositiondependent properties of CPs pertaining to their electrochemical characteristics can be tuned to design sensing motors capable of sensing their own working conditions without additional connectivity just as biological muscles do.…”
Section: Introductionmentioning
confidence: 99%